ACADEMIC STRESS LEADS ISSUES FOR ELEMENTARY STUDENT’S MENTAL HEALTH - Hanafiah, Hally; Khansa, Nisrina Khalisa (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Children are social beings with the same needs as adults, thus stress is something they will always encounter. They might experience fear or worry when faced with difficult situations. Children's stress typically stems from a variety of factors, including the strain of academics. Children with stress can exhibit physical and behavioral symptoms from academics including feelings of fear and anger, difficulty finishing tasks or receiving good grades, a load of crying, lack of appetite, and thoughts of harming themselves. Children who are under persistent stress may experience overload, melancholy, excessive worry, and physical and mental health disorders. The goal of this study is to lower the prevalence of early stress in children and school-age individuals, particularly in elementary school-aged students to develop optimal mental health as it ought to. This study's research approach is quantitative, and descriptive, and also involves literature review from some journals and a lot of data and information from articles. Data from questionnaire forms completed by 120 linked respondents, in total, are attached to this study. Additionally, the results of this study, which were derived from the data collection that was done, are known to indicate that a significant portion of children who completed elementary school in the past still experience academic stress, which can negatively impact the child and students' mental and physical health. Consequently, there is a need for initiatives or movements that might end these instances and problems to provide Indonesian society with a developed and healthy nation